TRANSFERRING CULTURAL KNOWLEDGE IN LOCAL NARRATIVE READING FOR EFL STUDENTS - Ferri Hidayad; Marleni Marleni (Universitas PGRI Palembang, 2021)
Indonesia has many narrative reading and different culture of many regions. Lacking of appreciation of own local culture is a continuing concern for many countries, including Indonesia. Through its constitution, the governement of Indonesia recommends that the education sector take part actively in preserving Indonesia local cultures. EFL teachers should use them in their teaching and learning process as one of the resources to apply to preserve culture for younger generations (EFL students). This research used local narrative reading to able the EFL teachers to preserve Indonesia culture as well as to transfer culture knowledge which makes their students study English and its culture with ease.